Wide-spectral-response radiation-resistant rod tube assembly and preparation method and application thereof

By adopting specially made wide spectrum response and irradiation-resistant mandrel glass and leather tube glass, and optimizing their performance differences and process parameters, the problem of insufficient wide spectrum response and irradiation resistance of fiber image transmission arrays in radiant environments is solved, and higher transmission efficiency and service life are achieved.

CN119774869AActive Publication Date: 2025-04-08CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411946312.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-08
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to meet the wide spectrum response and radiation resistance of fiber image transmission arrays in radiated environments, especially in terms of performance matching between mandrel glass and tube glass.

Method used

The special wide spectrum radiation-resistant mandrel glass and leather tube glass are used to adjust the difference in thermal expansion coefficient, softening temperature and refractive index to maintain chemical stability at 810°C. The high transmittance and radiation resistance of the glass are ensured by optimizing raw material ratio and process parameters.

Benefits of technology

It has achieved the improvement of the wide spectrum response and radiation resistance of fiber image transmission arrays, and met the requirements of long-distance detection and long service life in radiated environments such as aerospace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005213735420000161
    Figure BDA0005213735420000161
  • Figure BDA0005213735420000171
    Figure BDA0005213735420000171
  • Figure BDA0005213735420000181
    Figure BDA0005213735420000181
Patent Text Reader

Abstract

The invention provides a wide-spectral-response radiation-resistant rod and tube assembly and a preparation method and application thereof. The device comprises a core rod and a leather hose, the leather hose sleeves the outer side of the core rod; the spectrum transmittance of the core rod glass at 330-2000nm under 100mm is greater than or equal to 65%; the transmittance attenuation rate at 350nm is less than or equal to 3% under the irradiation of 6.4 kGy for 500h; the spectrum transmittance of the leather hose glass at 330-2000nm under 100mm is greater than or equal to 75%; the transmittance attenuation rate at 350nm is less than or equal to 3% under the irradiation of 6.4 kGy for 500h; the thermal expansion coefficient difference of the core and the skin is 1-10 * 10 <-7 > / DEG C; the softening temperature difference of the core and the skin is 10-25 DEG C; the refractive index difference value of the core and the skin is greater than 0.3; the core glass and the skin glass keep chemical stability at 810 DEG C. The technical problem to be solved is how to prepare the radiation-resistant rod-tube assembly with wide spectral response, so that the compatibility of a core rod and a leather tube is good, and the radiation-resistant rod-tube assembly can be used in the preparation of an optical fiber image transmission array, so that the radiation-resistant performance of the wide spectral response of the optical fiber image transmission array is improved. And the requirements of long-distance detection and long service life in ray irradiation environments in the aerospace field and the like are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical fiber manufacturing, and in particular to a wide spectrum response radiation-resistant rod-tube assembly and a preparation method and application thereof. Background Art

[0002] The fiber optic image transmission array is composed of tens of millions of micron-level optical fibers tightly and regularly arranged and fused together. It can transmit images with high fidelity and has the characteristics of zero optical thickness, large numerical aperture, high resolution, and strong light collection ability. It includes optical fiber panels, fiber optic image invertors, fiber optic light cones, fiber optic image transmission bundles, etc. It can be used in windows, optical coupling and display materials of photoelectric detection devices such as low-light level image intensifiers, photomultiplier tubes, X-ray image intensifiers, star sensors, and high-end radiation medical equipment. It is a high-tech and cutting-edge product in the optoelectronics industry.

[0003] The optical fiber image transmission array uses a core rod glass with a high refractive index and a skin tube glass tube with a low refractive index to arrange the plates by combining the rod and the tube with drawn single wires; the absorbent glass is drawn into wires and inserted into the arranged single wires. The absorbent glass mainly absorbs stray light; it is then bundled into a composite rod and subjected to wire drawing, plate arrangement, hot melt pressing to form a blank plate section, and then precision deep processing. It is mainly used to achieve high-definition image transmission, which solves the problem of low resolution and poor clarity of the system's field image, and improves the imaging clarity.

[0004] At present, fiber optic imaging arrays are used for long-distance detection in radiation-irradiated environments such as space. The fiber optic imaging array is required to have a wide spectrum and high transmittance to obtain a longer detection distance, and it is also required to be able to withstand radiation. It is difficult to meet both requirements at the same time. Core rod glass and skin tube glass are the core components of the optical fiber image transmission array, and their quality and performance have an important impact on the transmission effect of the optical fiber image transmission array; however, there is no core rod glass in the prior art that can simultaneously meet the three conditions of wide spectrum response, radiation resistance and high refractive index; the skin tube glass mainly functions to form a total reflection layer at the core-skin interface. Due to its smaller scale inside the optical fiber panel, it is more prone to defects during the manufacturing process, and must be better than the core rod glass in terms of radiation resistance and ultraviolet transmission performance; there is also no skin tube glass in the prior art that can simultaneously meet the three conditions of wide spectrum response, radiation resistance and low refractive index; the core rod glass and skin tube glass are combined into a rod and tube for the preparation of the optical fiber image transmission array, which requires more than 20 manufacturing processes for precision processing, so the performance matching of the core rod glass and the skin tube glass is crucial; however, there is no related report on wide spectrum response radiation-resistant rod and tube assemblies in the prior art. Summary of the invention

[0005] The main purpose of the present invention is to provide a wide spectrum response radiation-resistant rod-tube assembly and its preparation method and application. The technical problem to be solved is how to prepare a wide spectrum response radiation-resistant rod-tube assembly so that the core rod and the skin tube have good compatibility, so that it can be used in the preparation of optical fiber image transmission arrays, improve the wide spectrum response radiation resistance of the optical fiber image transmission array, meet the requirements of long-distance detection and long service life in radiation irradiation environments such as the aerospace field, and thus be more suitable for practical use.

[0006] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the invention, a wide spectrum response radiation-resistant rod-tube assembly includes a core rod and a skin tube; the skin tube is sleeved on the outside of the core rod; the glass of the core rod has a spectral transmittance of ≥65% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; the glass of the skin tube has a spectral transmittance of ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; wherein the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the skin tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass is 10-25℃; the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃.

[0007] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. According to the method for preparing a wide spectrum response radiation-resistant rod-tube assembly proposed by the present invention, the method comprises the following steps:

[0008] S21 raw materials are measured and mixed to obtain a core rod mixture and a leather tube mixture;

[0009] S22: melting the core rod mixture and the skin tube mixture respectively, clarifying and stirring, discharging, casting and annealing to obtain a core rod or a skin tube; the glass of the core rod has a spectral transmittance of ≥65% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; the glass of the skin tube has a spectral transmittance of ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose;

[0010] S23: The leather tube is placed on the outside of the core rod to obtain a rod-tube assembly; wherein the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the leather tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass is 10-25℃; the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃.

[0011] The purpose of the present invention and the solution to its technical problems can be further achieved by adopting the following technical measures.

[0012] Preferably, in the above-mentioned preparation method, the core rod mixture comprises, by weight percentage, 10-15% quartz sand, 20-30% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate, and 0.05-2% cerium oxide; the leather tube mixture comprises: 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1 potassium bifluoride, and 1 -8%, calcium fluoride 1-8%, basic magnesium carbonate 0-5%, lithium carbonate 0-8%, zinc oxide 0-5%, cerium oxide 0-2%; in the core rod mixture and the tube mixture, the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, Dy is ≤2ppm; the instruments for preparing and melting the core rod mixture are all made of non-metallic alkali-resistant materials; the instruments for preparing and melting the tube mixture are all made of non-metallic materials; oxygen is introduced into the glass liquid during the melting, clarifying and stirring steps; the melting furnace for melting and clarifying is made of refractory material, and its heavy metal content is ≤5ppm.

[0013] Preferably, in the aforementioned preparation method, the container for melting the core rod mixture is a crucible made of magnesium oxide; the container for melting the tube mixture is a crucible made of quartz, and the surface of the crucible is provided with a silicon oxide coating.

[0014] Preferably, in the aforementioned preparation method, the refractory material is a corrosion-resistant and high-temperature-resistant material, and its temperature resistance is ≥1700°C.

[0015] Preferably, in the aforementioned preparation method, the melting furnace for melting the core rod mixture is dedicated to the preparation of the core rod glass; or, the melting furnace for melting the skin tube mixture is dedicated to the preparation of the skin tube glass.

[0016] Preferably, in the aforementioned preparation method, the mixed material is melted by adding the mixed material into the container in 3-5 times, each time at an interval of 0.5-2 hours.

[0017] Preferably, in the aforementioned preparation method, the melting temperature of the core rod mixture is 1350-1400°C; the clarification and stirring temperature is 1460-1530°C, and the clarification and stirring temperature time is 1-2h; the discharge temperature is 1300-1350°C; the annealing temperature is 550-600°C, and the annealing time is 2-4h; or, the melting temperature of the leather tube mixture is 1350-1400°C; the clarification and stirring temperature is 1460-1530°C, and the clarification and stirring temperature time is 1-2h; the discharge temperature is 1300-1350°C; the annealing temperature is 550-600°C, and the annealing time is 2-4h.

[0018] Preferably, in the aforementioned preparation method, when preparing the core rod, the flow rate of oxygen introduced into the glass liquid is 0.1-0.3 mol / L / min; or, when preparing the leather tube, the flow rate of oxygen introduced into the glass liquid is 0.04-0.18 mol / L / min.

[0019] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: The present invention proposes the application of the wide spectrum response radiation resistant rod-tube assembly according to the previous description in the preparation of a wide spectrum response radiation resistant optical fiber image transmission array.

[0020] By means of the above technical solution, the wide spectrum response radiation-resistant rod-tube assembly and its preparation method and application proposed by the present invention have at least the following advantages:

[0021] The invention provides a wide spectrum response radiation-resistant rod-tube assembly and a preparation method and application thereof. The invention forms a rod-tube assembly by forming a core rod with a wide spectrum response and a radiation-resistant skin tube glass with a wide spectrum response into a skin tube, and sleeves the skin tube on the outside of the core rod; the rod-tube assembly has good processability by designing the performance matching of the core rod glass and the skin tube glass; specifically, the invention makes the thermal expansion coefficients of the core rod glass and the skin tube glass similar by designing the matching of the thermal expansion coefficients of the skin tube and the core rod, which can prevent the optical fiber from bursting due to the mismatch of the thermal expansion coefficients during the heating or cooling process of the glass, and can make the skin tube glass better attached to the core glass during the subsequent optical fiber drawing and heating process, and the skin layer can also generate a certain compressive stress during the drawing and cooling process to improve the strength of the optical fiber, ensure that compressive stress can be formed during the drawing process, and enhance the strength of the optical fiber; the invention can ensure that the core and skin layers are matched in the subsequent drawing process by designing the matching of the softening temperatures of the skin tube and the core rod. The roundness of the glass makes the skin material soften and bond during the pressing process, while the core material can still maintain a circular structure, thereby preventing the transmission light from leaking due to the deformation of the fiber core and not meeting the total reflection condition; the present invention matches the compatibility of the skin tube and the core rod, so that the core rod glass and the skin tube glass can still have good chemical compatibility near their respective lower temperature limits. The rod-tube assembly designed by the technical solution of the present invention is designed to have a maximum process temperature of about 810°C in the subsequent optical fiber plate making process. The present invention limits the core rod glass and the skin tube glass to be chemically stable at 810°C, that is, the two glasses will not penetrate, crystallize or phase separate when kept at 810°C for 5 hours, thereby better solving the problem of reduced transmittance caused by incomplete core-skin interface due to mutual penetration or crystallization and phase separation between the glasses during the process; the present invention limits the refractive index difference between the core rod glass and the skin tube glass to >0.3 by matching the compatibility of the optical properties of the skin tube and the core rod, thereby effectively improving the optical fiber imaging array light flux N A, which improves the transmission efficiency of the fiber optic imaging array and reduces the loss of images or signals during transmission, thereby improving the overall transmission quality of the fiber optic imaging array. As can be seen from the above, in the technical scheme of the present invention, by controlling the core rod glass to have a spectral transmittance of ≥65% in the wavelength range of 330-2000nm at a thickness of 100mm, and a transmittance attenuation rate of ≤3% at 350nm after irradiation for 500h at a irradiation dose of 6.4kGy, and controlling the skin tube glass to have a spectral transmittance of ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm, and a transmittance attenuation rate of ≤3% at 350nm after irradiation for 500h at a irradiation dose of 6.4kGy, so that it has good wide spectrum response and radiation resistance, and then through the better combination of the core rod glass and the skin tube glass, a rod-tube assembly with excellent comprehensive performance is prepared, so that it has good processability in the subsequent preparation of optical fiber image transmission elements, improves the wide spectrum response and radiation resistance of the optical fiber image transmission array, and meets the requirements of long-distance detection and long service life in radiation irradiation environments such as the aerospace field.

[0022] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION

[0023] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a wide spectrum response radiation-resistant rod-tube assembly and its preparation method and application according to the present invention, its specific implementation method, structure, features and effects in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0024] The present invention provides a wide spectral response radiation-resistant rod-tube assembly, which comprises a core rod and a skin tube, wherein the skin tube is sleeved on the outer side of the core rod; the structural design of the rod-tube assembly belongs to the conventional setting in the art; however, in the present invention, both the core rod glass and the skin tube glass are glasses with wide spectral response and radiation resistance, wherein the core rod glass has a spectral transmittance of ≥65% in a wavelength range of 330 to 2000 nm at a thickness of 100 mm; and a transmittance attenuation rate of ≤3% at 350 nm after irradiation for 500 h at a 6.4 kGy irradiation dose; the skin tube glass has a spectral transmittance of ≥75% in a wavelength range of 330 to 2000 nm at a thickness of 100 mm; and a transmittance attenuation rate of ≤3% at 350 nm after irradiation for 500 h at a 6.4 kGy irradiation dose; that is, both the core rod glass and the skin tube glass have better radiation resistance, and the transmittance of the skin tube glass is higher than that of the core rod glass.

[0025] When two types of glass are combined to form a rod-tube assembly, the performance matching of the two types of glass is very critical. First, if the two types of glass are not well matched, the fiber interface may be uneven. When light propagates on these uneven interfaces, scattering will occur, resulting in optical signal loss and reducing the light collection ability of the fiber image transmission array; second, if the thermal expansion coefficients of the core rod glass and the tube glass do not match, the core glass will be subjected to excessive compressive stress or tensile stress during the heat treatment process, reducing the strength of the optical fiber and destroying the roundness and structure of the optical fiber; third, if the softening temperatures of the core rod glass and the tube glass do not match, the fiber core will be deformed during the pressing process, not meeting the total reflection conditions and causing light leakage; fourth, if the viscosity of the core rod glass and the tube glass does not match, the softening degree of the two types of glass will be inconsistent during the drawing process, which is not conducive to fiber drawing; fifth, if the chemical compatibility of the core rod glass and the tube glass is poor, the glass will penetrate each other or crystallize and separate during the plate making process, resulting in an incomplete core-skin interface and a reduction in transmittance. Therefore, in addition to ensuring the high refractive index of the core rod glass and the low refractive index of the skin tube glass, the performance matching of the two glasses is also critical.

[0026] The present invention limits the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the skin tube glass to 1×10 -7 / ℃~10×10 -7 / ℃; through the performance matching design of the core rod glass and the skin tube glass, the thermal expansion coefficients of the core rod glass and the skin tube glass are made similar, which can prevent the optical fiber from bursting due to the mismatch of thermal expansion coefficients during the heating or cooling process of the glass, and on the other hand, in the subsequent optical fiber drawing and heating process, the skin layer can better adhere to the core glass, and in the drawing and cooling process, the skin layer can also produce a certain compressive stress, thereby improving the strength of the optical fiber, ensuring that compressive stress can be formed during the drawing process, and enhancing the strength of the optical fiber yarn; the present invention limits the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass to 10-25℃, which can ensure that the core and skin glass in the subsequent drawing process The roundness of the glass is improved, so that the skin material softens and bonds during the pressing process, while the core material can still maintain a circular structure, thereby preventing the transmission light from leaking due to the deformation of the fiber core and failure to meet the total reflection condition; the present invention limits the core rod glass and the skin tube glass to be chemically stable at 810°C, that is, the two glasses will not penetrate, crystallize or separate when kept at 810°C for 5 hours, thereby effectively solving the problem of reduced transmittance caused by incomplete core-skin interface due to mutual penetration or crystallization and phase separation between the glasses during the process; the present invention limits the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass to more than 0.3; thereby effectively improving the optical fiber imaging array light flux N A, which improves the transmission efficiency of the fiber optic imaging array and reduces the loss of images or signals during transmission, thereby improving the overall transmission quality of the fiber optic imaging array.

[0027] Through the limitation of the above technical scheme, the present invention can obtain a rod-tube assembly with wide spectral response and radiation resistance, so that it has good processability in the subsequent preparation of optical fiber imaging elements, improves the wide spectral response and radiation resistance of the optical fiber imaging array, and meets the requirements of long-distance detection and long service life in radiation irradiation environments such as the aerospace field.

[0028] The present invention also proposes a method for preparing a wide spectrum response radiation-resistant rod-tube assembly, which includes the following steps: first, a core rod and a leather tube are prepared. Specifically, the method includes: raw material metering and mixing to obtain a core rod mixture and a leather tube mixture; respectively melting the core rod mixture and the leather tube mixture, clarifying and stirring, discharging, casting and forming, and annealing to obtain a core rod or a leather tube. The specific description is as follows:

[0029] In some specific embodiments of the present invention, the core rod mixture includes, by mass percentage, 10-15% quartz sand, 20-30% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate, and 0.05-2% cerium oxide, wherein the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, and Dy is ≤2ppm. The core rod mixture is melted, clarified, stirred, formed and annealed to obtain a core rod; each component in the core rod exists in the form of oxides, that is, it contains SiO2, B2O3, La2O3, ZnO, Nb2O5, BaO, HfO2, Ta2O5, Y2O3, SrO, Al2O3, Na2O, and CeO2.

[0030] In the core rod glass, SiO2 is introduced in the form of quartz sand, which is the main body of the glass skeleton and the main component of the glass skeleton. In the core rod glass, the weight percentage of the quartz sand raw material is 10-15%. When the quartz sand raw material content is less than 10%, it is difficult to obtain a glass with a high refractive index, and the chemical resistance of the glass will also be reduced; when the quartz sand raw material content is higher than 15%, the high-temperature viscosity of the glass will increase, resulting in an excessively high glass melting temperature, and the thermal expansion coefficient of the glass will also be reduced.

[0031] B2O3 is introduced in the form of boric acid, which is an oxide for glass formation and also a component of the glass skeleton. It is also a solvent that reduces the viscosity of glass melting. Boron oxide triangle [BO3] and boron oxide tetrahedron [BO4] are structural components. Boron may exist in the form of triangle [BO3] or boron oxide tetrahedron [BO4] under different conditions. Under high temperature melting conditions, it is generally difficult to form boron oxide tetrahedron, and it can only exist in the form of trihedron. However, at low temperature, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, it is also the main component that reduces the refractive index of the glass, which determines that its content range is relatively small. The preferred weight percentage of the boric acid raw material in the core rod glass is 20-30%. When the content of the boric acid raw material is less than 20%, it cannot play a dissolving role and will also reduce the chemical stability of the glass; when the content of the boric acid raw material is greater than 30%, the refractive index of the glass will be reduced and the phase separation tendency of the glass will also increase.

[0032] La2O3 is introduced as lanthanum oxide, which is a lanthanum series rare earth oxide and can increase the refractive index of glass. The weight percentage of lanthanum oxide is preferably 19.5-30%, but when the lanthanum oxide content is greater than 30%, the thermal expansion coefficient of the glass will increase.

[0033] ZnO is introduced as zinc oxide, with a high bandgap and excitation binding energy, and a high absorption coefficient under certain rays. A small amount of introduction can improve the radiation resistance of glass. The weight percentage of zinc oxide is 1.1-10%. When the content of ZnO is greater than 10%, it will reduce the chemical resistance and thermal expansion coefficient of the glass and increase the tendency of crystallization.

[0034] Nb2O5 is introduced as niobium oxide, which is also a rare earth oxide. It can increase the refractive index of glass and replace part of La2O3. According to the particle hybridization theory, the introduction of multiple particles can improve the stability of the glass structure. The weight percentage of niobium oxide is 1.1-10%, but when the niobium oxide content is greater than 10%, the density and thermal expansion coefficient of the glass will increase.

[0035] BaO is introduced in the form of barium carbonate, which is an external oxide of the glass structure network. It has a high absorption coefficient under certain rays and can improve the radiation resistance of the glass. The weight percentage of the barium carbonate raw material is preferably 10.1-20%. The content of the barium carbonate raw material is greater than 20%, which will increase the crystallization temperature of the glass and increase the crystallization tendency of the glass.

[0036] HfO2 is introduced as hafnium oxide. HfO2 has a wide transparent range from ultraviolet (UV) to infrared (IR), which makes the glass have a good light transmittance foundation in the ultraviolet band and allows ultraviolet light to pass through the glass more easily. The weight percentage of hafnium oxide is 0-3%, but when the hafnium oxide content is greater than 3%, the chemical balance of the glass will be destroyed and the glass will be prone to crystallization.

[0037] Ta2O5 is introduced as tantalum oxide, which is also a rare earth oxide. It can increase the refractive index of glass and replace part of La2O3. According to the particle hybridization theory, the introduction of multiple particles can improve the stability of the glass structure. The weight percentage of tantalum oxide is 5.1-10%, but when the tantalum oxide content is greater than 10%, the density and thermal expansion coefficient of the glass will increase.

[0038] Y2O3 is introduced as yttrium oxide, which is also a rare earth oxide. It can increase the refractive index of glass and replace part of La2O3. According to the particle hybridization theory, the introduction of multiple particles can improve the stability of the glass structure. The weight percentage of yttrium oxide is 1.1-7%, but when the yttrium oxide content is greater than 7%, the density and thermal expansion coefficient of the glass will increase.

[0039] SrO is introduced in the form of strontium carbonate, which is an alkaline earth metal oxide and an external oxide of the glass structure network. It has a high absorption coefficient under certain rays and can improve the radiation resistance of the glass. The weight percentage of the strontium carbonate raw material is preferably 0-5%. When the content of the strontium carbonate raw material is greater than 5%, the chemical stability of the glass will be reduced and the thermal expansion coefficient of the glass will be increased.

[0040] Al2O3 is introduced as aluminum oxide, which is an intermediate oxide of glass. It can improve the radiation resistance of glass and reduce the phase separation tendency of glass. 3+ Prioritizes the formation of free oxygen [AlO4], which enters the glass network. 3+ Occupy Si 4+ Due to Al 3+ and Si 4+ There are different valence states, which require alkali metal ions to fill and balance the valence state. The broken structural chains in the glass are linked again, the structure of the glass tends to be compact, the number of non-bridging oxygen is reduced, and the radiation resistance of the glass is improved. Therefore, within a certain content range, it can become the main body of glass network formation like SiO2. The weight percentage of aluminum oxide is 0.5-7%. When the content of aluminum oxide is greater than 7%, the high-temperature viscosity of the glass will be significantly increased, and the melting temperature of the glass will be increased.

[0041] Na2O is introduced in the form of sodium carbonate, which is an alkali metal oxide and an external oxide of the glass structure network. Na2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. The weight percentage of the sodium carbonate raw material is preferably 0-5%. When the content of the sodium carbonate raw material is greater than 5%, the refractive index and thermal expansion coefficient of the glass will increase, and the crystallization tendency of the glass will increase.

[0042] CeO2 is introduced with cerium oxide, which is a rare earth oxide. Cerium is a variable valence element and is in a high valence state under irradiation. 4+ It can first absorb high-energy electrons or free electrons caused by radiation, causing the valence state of the ions to change without causing the establishment of color centers, thereby playing a role in radiation resistance. However, after the valence of the cerium element changes, the element absorbs ultraviolet and visible light in the new valence state, which will also cause the transmittance of the optical fiber imaging array to decrease. 4+ It has strong absorption in the visible light region and is converted into Ce 3+ When the absorption in the spectral region above 300nm is very small. The appropriate amount of Ce element introduced, through the oxygen-enriched melting process, accurately controls the valence state of the element, so that the amount of cerium introduced can be minimized under the premise that the radiation resistance meets the requirements, thereby resolving the contradiction between ultraviolet transparency (no valence element in the composition as much as possible) and radiation resistance (introducing cerium, the valence element, into the composition to absorb high-energy electrons generated after high-energy radiation to avoid the formation of color centers), achieving radiation resistance while ensuring that the glass has a high transmittance in the ultraviolet region. The weight percentage of cerium oxide is 0.05-2%. When the content of cerium oxide is greater than 2%, the crystallization tendency of the glass will increase and the transmittance of the glass will also be reduced.

[0043] In some specific embodiments of the present invention, the leather tube mixture includes, by mass percentage, 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1-8% potassium bifluoride, 1-8% calcium fluoride, 0-5% basic magnesium carbonate, 0-8% lithium carbonate, 0-5% zinc oxide, 0-2% cerium oxide, wherein the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, Dy is ≤2ppm. The leather tube mixture is melted, clarified, stirred, molded, and annealed to obtain a leather tube; each component in the leather tube exists in the form of oxides, that is, it contains SiO2, B2O3, Al2O3, Na2O, K2O, CaO, MgO, Li2O, ZnO, and CeO2.

[0044] In the above-mentioned leather tube glass, SiO2 is introduced in the form of quartz sand, which is the main body of the glass skeleton and the main component in the glass skeleton. In the leather tube glass, the weight percentage of quartz sand is 60-75%. When the content of quartz sand raw material is lower than 60%, it is difficult to obtain low refractive index glass, and the chemical resistance stability of the glass will also be reduced; when the content of quartz sand raw material is higher than 75%, the high temperature viscosity of the glass will increase, resulting in excessively high glass melting temperature, and the thermal expansion coefficient of the glass will also be reduced.

[0045] B2O3 is introduced in the form of boric acid, which is an oxide for glass formation and also a component of the glass skeleton. It is also a solvent that reduces the viscosity of glass melting. Boron oxide triangle [BO3] and boron oxide tetrahedron [BO4] are structural components. Boron may exist in the form of triangle [BO3] or boron oxide tetrahedron [BO4] under different conditions. Under high temperature melting conditions, it is generally difficult to form boron oxide tetrahedron, and it can only exist in the form of trihedron. However, at low temperature, under certain conditions, B 3+ It has a tendency to capture free oxygen to form tetrahedrons, making the structure compact and increasing the low-temperature viscosity of the glass. However, due to its characteristics of reducing the viscosity of the glass at high temperatures and increasing the viscosity of the glass at low temperatures, it is also the main component that reduces the refractive index of the glass, which determines that its content range is relatively small. The preferred weight percentage of the boric acid raw material in the leather tube glass is 1.5-15. When the content of the boric acid raw material is greater than 15%, the refractive index of the glass will be reduced, and the phase separation tendency of the glass will also be increased.

[0046] Al2O3 is introduced as aluminum oxide, which is an intermediate oxide of glass. It can improve the radiation resistance of glass and reduce the phase separation tendency of glass. 3+ Prioritizes the formation of free oxygen [AlO4], which enters the glass network. 3+ Occupy Si 4+ Due to Al 3+ and Si 4+ There are different valence states, which require alkali metal ions to fill and balance the valence state. The broken structural chains in the glass are linked again, the structure of the glass tends to be compact, the number of non-bridging oxygen is reduced, and the radiation resistance of the glass is improved. Therefore, within a certain content range, it can become the main body of glass network formation like SiO2. The weight percentage of aluminum oxide is 1-5%. When the content of aluminum oxide is greater than 5%, the high-temperature viscosity of the glass will be significantly increased, and the melting temperature of the glass will be increased.

[0047] Na2O is introduced in the form of sodium carbonate, which is an alkali metal oxide and an external oxide of the glass structure network. Na2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. The weight percentage of the sodium carbonate raw material is preferably 1-10%. When the raw material content of sodium carbonate is greater than 10%, the refractive index and thermal expansion coefficient of the glass will increase, and the crystallization tendency of the glass will increase.

[0048] K2O is introduced in the form of potassium bifluoride, which is an alkali metal oxide and an external oxide of the glass structure network. K2O repairs the breakpoint between [SiO4] and [BO3], transforms the [BO3] triangular layered structure into a [BO4] tetrahedron, strengthens the network connection, increases the number of bridging oxygen, and moves the ultraviolet intrinsic absorption to the short-wave direction, thereby improving the wide spectrum transmittance of the glass. - The introduction of F can fill the oxygen vacancies in the glass, repair the structural defects and improve the glass transmittance. - The 8-electron structure is stabilized by using its strong binding effect on the outer electrons to reduce the number of high-energy free electrons generated by irradiation, avoid the formation of color centers, and improve the radiation resistance of the glass. The weight percentage of the potassium bifluoride raw material is preferably 1-8%. When the content of the potassium bifluoride raw material is greater than 8%, the refractive index and thermal expansion coefficient of the glass will be increased, and the crystallization tendency of the glass will be increased.

[0049] CaO is introduced in the form of calcium fluoride to improve the radiation resistance and wide spectrum transmittance of the glass. - The introduction of F can fill the oxygen vacancies in the glass, repair the structural defects and improve the glass transmittance. - In order to stabilize the 8-electron structure, the strong binding effect on the outer electrons is utilized to reduce the number of high-energy free electrons generated by irradiation, avoid the formation of color centers, and improve the radiation resistance of the glass. The weight percentage of calcium fluoride raw materials is 1-8%. When the calcium fluoride content is greater than 8%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.

[0050] MgO is introduced in the form of basic magnesium carbonate, which is an external oxide of the glass structure network and is used to adjust the crystallization temperature of the glass. The weight percentage of the basic magnesium carbonate raw material is 0-5%. If the content of the basic magnesium carbonate raw material is greater than 5%, the crystallization tendency of the glass will be increased.

[0051] Li2O is introduced in the form of lithium carbonate and is an external oxide in the glass structure network. Lithium oxide has a small ionic radius and high electronegativity, and is easy to enter the glass structure network and exert a greater attraction on the surrounding molecules, which helps to densify the glass structure, reduce internal defects and scattering centers, and thus improve the transmittance of the glass. The weight percentage of lithium carbonate raw materials is 0-8%. When the content of lithium carbonate raw materials is greater than 8%, the expansion coefficient of the glass will be increased.

[0052] ZnO is introduced as zinc oxide, with a high bandgap and excitation binding energy, and a high absorption coefficient under certain radiation exposure. A small amount of introduction can improve the radiation resistance of glass. The weight percentage of zinc oxide is 0-5%. When the zinc oxide content is greater than 5%, the chemical resistance and thermal expansion coefficient of the glass will be reduced, and the tendency of crystallization will be increased.

[0053] CeO2 is introduced with cerium oxide, which is a rare earth oxide. Cerium is a variable valence element and is in a high valence state under irradiation. 4+ It can first absorb high-energy electrons or free electrons caused by radiation, causing the valence state of the ions to change without causing the establishment of color centers, thereby playing a role in radiation resistance. After the cerium element changes its valence, the element absorbs ultraviolet and visible light in the new valence state, which will also cause the transmittance of the optical fiber imaging array to decrease. 4+ It has strong absorption in the visible light region and is converted into Ce 3+ When the absorption in the spectral region above 300nm is very small. The appropriate amount of Ce element introduced, through the oxygen-enriched melting process, accurately controls the valence state of the element, so that the amount of cerium introduced can be minimized under the premise that the radiation resistance meets the requirements, thereby resolving the contradiction between ultraviolet transparency (no valence element in the composition as much as possible) and radiation resistance (introducing cerium, the valence element, into the composition to absorb high-energy electrons generated after high-energy radiation to avoid the formation of color centers), achieving radiation resistance while ensuring that the glass has a high transmittance in the ultraviolet region. The weight percentage of cerium oxide is 0-2%. When the content of cerium oxide is greater than 2%, the crystallization tendency of the glass will increase and the transmittance of the glass will also be reduced.

[0054] In the above steps of preparing the core rod and the leather tube, the purity control of the raw materials is very critical, because the harmful impurities that may exist in the raw materials, such as transition metal valence ions and heavy metal ions, have low electron transition energy, and their electrons absorb energy and undergo transition under high-energy radiation, and have obvious absorption of ultraviolet rays in the ultraviolet region. Therefore, in order to avoid their influence on the transmittance of the glass material in the ultraviolet region, the present invention strictly controls the content of harmful impurities in the oxides or salts used to prepare the core rod and the leather tube. When preparing the mixture, all raw materials are high-purity raw materials, and the content of Fe, Cu, Mn, etc. in the raw materials is strictly controlled, so that the content of coloring elements in all raw materials is controlled below 3ppm; when using rare earth oxides such as Y, La, Ta, Nb, Ce, etc., the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, Dy, etc. is strictly prohibited, and the total content is controlled below 2ppm; thereby ensuring that the glass prepared by this technical solution has excellent comprehensive performance.

[0055] Furthermore, this step requires very high purity of the raw materials, so the containers and tools used in the batching process also need to be strictly controlled. For example, the material of the container for preparing the core rod mixture is strictly controlled to be a non-metallic alkali-resistant material; the material of the container for preparing the leather tube mixture is strictly controlled to be a non-metallic material; if it is a plastic product, it is preferably colorless and transparent; the reason for this arrangement is that: since the container, such as a crucible, will be in direct contact with the glass, whether it is the crucible material or impurities in the crucible, if they are brought into the mixture, they may melt into the glass during the subsequent melting process, which will have an adverse effect on the quality and performance of the glass. For example, if a platinum crucible is used, platinum particles or ions may enter the glass, which will cause ultraviolet absorption to be detrimental to the light transmittance of the glass; in addition On the one hand, depending on the acidity and alkalinity of the glass, if the glass composition does not match the material of the container, the glass composition may cause serious erosion to the container, thereby causing the glass components to be seriously affected and changed, and may even cause leakage of the container due to the erosion of the glass, such as leakage of the crucible, which may be very unfavorable to improving the quality of glass melting; the core rod glass component of the present invention is a silicon-boron-lanthanum-barium system, which is generally alkaline, so it has a heavier erosion effect on quartz crucibles and corundum crucibles. In view of this, the container of the core rod glass of the present invention is preferably no longer a platinum crucible, but a crucible made of magnesium oxide; according to the composition of the leather tube glass in the present invention, a quartz crucible is preferably used, and a high-purity silicon oxide coating is provided on the surface of the crucible, thereby reducing the influence of the crucible component on the glass component and reducing the introduction of impurities.

[0056] In the step of melting the mixture, the mixture can be melted by directly adding the mixture into a container for melting; however, in order to improve the melting efficiency and the quality of the molten glass, the present invention preferably adds the mixture into the melting container in batches during melting; in some specific embodiments of the present invention, the mixture is preferably added into the container in 3-5 times, each time with an interval of 0.5-2 hours; adding the mixture in batches in this way can more efficiently complete the melting of the glass composition.

[0057] The melting process of the glass mixture can be specifically adjusted according to its composition and ingredients. Under the composition formula conditions designed in the technical solution of the present invention, the melting temperature of the core rod mixture is preferably 1450-1520°C, and the melting temperature of the leather tube core rod mixture is preferably 1350-1400°C, so that the glass composition can be melted quickly.

[0058] After the glass mixture is completely melted, the glass liquid can be clarified and stirred. In this step, the clarification and stirring temperature of the core rod glass is preferably 1520-1600°C, and the clarification and stirring temperature time is 1-2h; during the clarification process of the glass liquid, forced stirring is preferably performed throughout the process; the material of the agitator is preferably a non-metallic alkali-resistant material to avoid contact with the glass liquid and the introduction of harmful impurities. The clarification and stirring temperature of the leather tube glass is preferably 1460-1530°C, and the clarification and stirring temperature time is 1-2h; during the clarification process of the glass liquid, stirring is preferably performed throughout the process; the material of the agitator is preferably a non-metallic material to avoid contact with the glass liquid and the introduction of harmful impurities. In the above-mentioned clarification step, it is preferred that the agitator uses a double-blade paddle to improve the stirring effect.

[0059] In order to ensure that the obtained glass can have a high transmittance under irradiation conditions, the present invention strictly limits the introduction of oxygen into the glass melt during the glass melting, clarification and stirring stages so that the glass melt can be in a strong oxidizing atmosphere. The amount of oxygen introduced will adjust the concentration of the oxidizing atmosphere of the glass melt so that the variable valence element can be melted in an oxygen-rich environment, so that the glass melt has a sufficient amount of high-valence variable valence elements to meet the radiation resistance of the glass, and at the same time, the amount of high-valence variable valence elements will not be too high, resulting in the absorption of light by high-valence variable elements and affecting the transmittance of the glass. In some specific embodiments of the present invention, the flow rate of oxygen introduced into the glass melt by the core rod glass is preferably 0.1-0.3 mol / L / min, and the flow rate of oxygen introduced into the glass melt by the leather tube glass is preferably 0.04-0.18 mol / L / min, so that the valence state of the radiation-resistant variable valence element cerium can be accurately adjusted to ensure that the core rod glass has a high transmittance and high radiation resistance under irradiation conditions.

[0060] The melting of glass is generally carried out in an open crucible. Since the decomposition of the raw materials in the glass mixture may produce a large amount of volatilized gas, and some components in the glass composition are also volatile, these volatile components will corrode the materials of the melting furnace, and the corroded materials may also affect the glass itself through the crucible mouth. For this reason, the present invention preferably uses a refractory material as the material of the melting and clarification melting furnace, and strictly controls the content of heavy metals such as lead, cadmium, and mercury to ≤5ppm, thereby directly reducing the adverse effects of the melting furnace material on the quality of the glass liquid; further, by preferably using the refractory material as a corrosion-resistant and high-temperature resistant material, preferably with a temperature resistance of ≥1700°C, it can avoid or reduce the corrosion of the volatile components of the glass on the melting furnace, thereby indirectly reducing the adverse effects of the melting furnace material on the quality of the glass liquid.

[0061] Furthermore, in order to avoid cross-contamination of glass due to erosion of the refractory materials of the melting furnace, the present invention preferably uses a dedicated melting furnace for heating the container, that is, the melting furnace for preparing core rod glass is only used for melting core rod glass of this formula, and the melting furnace for preparing skin tube glass is only used for melting skin tube glass of this formula, thereby avoiding or reducing cross-contamination caused by the melting furnace material; the present invention may further preferably replace it regularly according to usage and erosion conditions, so as to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass, thereby avoiding or reducing the influence of the melting furnace on the composition of the glass liquid.

[0062] The core rod glass liquid is discharged by injecting the glass liquid into the core rod mold and casting it into the core rod glass of the required specifications; after annealing, the core rod can be obtained. The leather tube glass liquid is discharged by injecting the glass liquid into the leather tube mold and casting it into the leather tube glass of the required specifications; after annealing, the leather tube can be obtained. The temperature and time of the glass liquid discharge, molding and annealing can be adjusted according to the actual composition of the glass composition. In some specific embodiments of the present invention, according to the composition of the glass composition, the discharge temperature of the core rod glass is preferably 1360-1400℃, the annealing temperature is 600-650℃, and the annealing time is 2-4h; the discharge temperature of the leather tube glass is preferably 1300-1350℃, the annealing temperature is 550-600℃, and the annealing time is 2-4h.

[0063] Finally, the leather tube is placed on the outside of the core rod to obtain a rod-tube assembly; wherein the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the leather tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass is 10-25℃; the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃.

[0064] The present invention also proposes an application of the wide spectrum response radiation resistant rod-tube assembly described above in the preparation of a wide spectrum response radiation resistant optical fiber image transmission array.

[0065] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.

[0066] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.

[0067] 1. Preparation of core rod glass:

[0068] Raw material requirements: quartz sand (4N, 160μm sieve oversize is less than 5%, 40μm sieve undersize is less than 5%), boric acid (analytical grade, 400μm sieve oversize is less than 10%, 63μm sieve undersize is less than 10%), strontium carbonate (analytical grade, purity ≥99.0%), lanthanum oxide (5N), niobium oxide (5N), yttrium oxide (5N), tantalum oxide (5N), zinc oxide (analytical grade), aluminum oxide (analytical grade, average particle size 50μm), sodium carbonate (analytical grade), barium carbonate (analytical grade), hafnium oxide (analytical grade), cerium oxide (4N), impurities in high-purity reagent raw materials are strictly controlled to have a total content of coloring elements such as Fe, Cu, and Mn <3ppm; when using rare earth oxides such as Y, La, Ta, and Nb, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, and Dy is strictly prohibited, and the total content is controlled to be <2ppm.

[0069] Example 1-1

[0070] Melting of core rod glass: Select raw materials according to the glass composition of Example 1-1 in Table 1-1, weigh the raw materials according to the ingredient list, mix them evenly and put them into a magnesium oxide crucible. The containers and utensils used in the batching and material processing are all made of non-metallic materials, and the plastic products are colorless and transparent. The content of lead, cadmium and mercury in the refractory material of the furnace top is controlled below 5ppm, and it is resistant to corrosion and high temperature above 1700℃. The melting electric furnace must be dedicated to avoid cross contamination caused by erosion of the refractory material. It should be replaced regularly according to the use and corrosion conditions to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass.

[0071] The mixture is added to the crucible 4 times every 1 hour for high temperature melting at 1500℃. After the raw material mixture is melted, it is clarified and stirred at a temperature of 1550℃ for 1.5 hours. The stirrer adopts a double-blade paddle to improve the stirring effect. During this melting and clarification stage, the oxygen valve is opened to introduce oxygen into the glass liquid at a flow rate of 0.2mol / L / min to make the glass liquid present a strong oxidizing atmosphere. The molten and clarified glass liquid is discharged at 1370℃ and cast into the required glass in a mold. After the glass is cooled and solidified, it is annealed at an annealing temperature of 640℃ and a heat preservation time of 2.5 hours to obtain the core rod glass of the present invention.

[0072] After testing, the core rod glass prepared in this embodiment has a spectral transmittance of 67% in the wavelength range of 330-2000nm at a thickness of 100mm; a transmittance attenuation rate of 2.6% at 350nm after irradiation for 500h at a dose of 6.4kGy; a refractive index of 1.8023; and an average linear thermal expansion coefficient of 91.0×10 -7 / ℃; kept at 810℃ for 5 hours without crystallization.

[0073] Example 1-2 to Example 1-5

[0074] The process is the same as that of Example 1-1. The core rod glass composition formula, raw material purity and process parameters are shown in Table 1. The test results are also shown in Table 1.

[0075] Table 1 Chemical composition, process parameters and properties of core rod glass of Examples 1-1 to 1-5

[0076]

[0077]

[0078] Note: a′ represents the total content of Fe, Cu, Mn and other coloring elements in high-purity reagent quartz sand, lanthanum oxide, niobium oxide, yttrium oxide, tantalum oxide and cerium oxide, in ppm; b′ represents the total content of Nd, Pr, U, Er, Eu, Tb and Dy impurities in rare earth oxides of lanthanum oxide, niobium oxide, yttrium oxide, tantalum oxide and cerium oxide, in ppm; c′ represents the spectral transmittance of 330nm~2000nm, in %; d′ represents the transmittance attenuation rate (irradiated for 500h at 6.4kGy irradiation dose, at 350nm), in %; e′ represents the refractive index; f′ represents the average linear thermal expansion coefficient in the range of 30~300℃, in ×10 -7 / ℃.

[0079] 2. Preparation of leather tube glass:

[0080] Raw material requirements: quartz sand (4N, 160μm sieve material is less than 5%, 40μm sieve material is less than 5%), boric acid (analytical grade, 400μm sieve material is less than 10%, 63μm sieve material is less than 10%), zinc oxide (analytical grade), aluminum oxide (analytical grade, average particle size 50μm), sodium carbonate (analytical grade), potassium bifluoride (analytical grade), calcium fluoride (analytical grade), basic magnesium carbonate (chemically pure, average particle size 50μm), lithium carbonate (analytical grade), cerium oxide (4N). The total content of Fe, Cu, and Mn coloring elements in high-purity raw materials is strictly controlled to be less than 3ppm. When rare earth cerium oxide is used, the introduction of impurity elements such as Nd, Pr, U, Er, Eu, Tb, and Dy is strictly prohibited, and the total content is controlled to be less than 2ppm.

[0081] Example 2-1

[0082] Melting of leather tube glass: Select raw materials according to the glass composition of Example 2-1 in Table 2, weigh the raw materials according to the ingredient list, mix them evenly and put them into a quartz crucible with a high-purity silicon oxide coating on the surface. The containers and utensils used in the batching and chemical process are all made of non-metallic materials, and the plastic products are colorless and transparent. The content of lead, cadmium and mercury in the refractory material of the furnace top is controlled below 5ppm, and it is resistant to corrosion and high temperature above 1700℃. The smelting electric furnace must be dedicated to avoid cross contamination caused by erosion of the refractory material. It should be replaced regularly according to the use and corrosion conditions to prevent harmful impurities such as Fe and Ti in the refractory material from entering the glass.

[0083] The mixture is added to the crucible 5 times at intervals of 0.5 hours for high temperature melting at 1360°C. After the raw material mixture is melted, it is clarified and stirred at a temperature of 1470°C for 2 hours. The stirrer adopts a double-blade paddle to improve the stirring effect. During this melting and clarification stage, the oxygen valve is opened to introduce oxygen into the glass liquid at a flow rate of 0.044 mol / L / min to make the glass liquid present a strong oxidizing atmosphere. The molten and clarified glass liquid is discharged at 1300°C and cast into the required glass in a mold. After the glass is cooled and solidified, it is annealed at an annealing temperature of 550°C and a heat preservation time of 4 hours to obtain the leather tube glass of the present invention.

[0084] After testing, the leather tube glass prepared in this embodiment has a spectral transmittance of 75.8% in the wavelength range of 330-2000nm at a thickness of 100mm; a transmittance attenuation rate of 2.3% at 350nm after irradiation for 500h at a dose of 6.4kGy; a refractive index of 1.4985; and an average linear thermal expansion coefficient of 82×10 -7 / ℃; kept at 910℃ for 5 hours without crystallization.

[0085] Example 2-2 to Example 2-5

[0086] The process is the same as that of Example 2-1. The formula of the leather tube glass composition, the purity of the raw materials and the process parameters are shown in Table 2, and the test results are also shown in Table 2.

[0087] Table 2 Chemical composition, process parameters and properties of leather tube glass of Examples 2-1 to 2-5

[0088]

[0089]

[0090] Note: a represents the total content of Fe, Cu, Mn and other coloring elements in high-purity reagent quartz sand and cerium oxide, in ppm; b represents the total content of Nd, Pr, U, Er, Eu, Tb, Dy impurities in cerium oxide, in ppm; c represents the spectral transmittance of 330nm~2000nm, in %; d represents the transmittance attenuation rate (irradiated for 500h at 6.4kGy irradiation dose, at 350nm), in %; e represents the refractive index; f represents the average linear thermal expansion coefficient in the range of 30~300℃, in ×10 -7 / ℃.

[0091] 3. Preparation of rod and tube assemblies

[0092] Examples 3-1 to 3-16 and Comparative Examples 1 to 9

[0093] The core rods prepared in Examples 1-1 to 1-5 and the leather tubes prepared in Examples 2-1 to 2-5 were respectively combined to obtain rod-tube assemblies, wherein the outer diameter of the core rod is 30.0-32.0 mm, the inner diameter of the leather tube is 30.5-32.5 mm, the thickness of the leather tube is 3.2-4.2 mm, and the difference between the outer diameter of the core rod and the inner diameter of the leather tube is 0.5 mm; the core-skin performance compatibility results are shown in Table 3.

[0094] The single filament is drawn at a temperature of 780-800°C and a rod lowering speed of 1.0-1.5 mm / min, the first multifilament is drawn at a temperature of 820-840°C and a rod lowering speed of 1.4-2.0 mm / min, the second multifilament is drawn at a temperature of 810-820°C and a rod lowering speed of 1.0-1.5 mm / min, the sheets are arranged, hot melt pressed at 600-650°C, and finely processed to prepare them into optical fiber imaging arrays; the machinability of each group of rod-tube assemblies and the quality of the optical fiber imaging arrays prepared therefrom are evaluated, and the results are shown in Table 3.

[0095] Table 3 Various properties of core rod glass and leather tube glass examples

[0096]

[0097]

[0098] It can be seen from the test data shown in Table 1 that the comprehensive performance of the core rod glass prepared in the embodiment of the present invention is excellent, and it simultaneously meets the requirements of wide spectrum response, radiation resistance and high refractive index, and has a high transmittance in the ultraviolet region. It can be seen from the test data shown in Table 2 that the comprehensive performance of the skin tube glass prepared in the embodiment of the present invention is excellent, and it simultaneously meets the requirements of wide spectrum response, radiation resistance and low refractive index, and has a high transmittance in the ultraviolet region. It can be seen from the test data shown in Table 3 that the optical fiber filaments of Comparative Examples 4, 6, 7 and 9 after drawing are broken. The reason may be that the thermal expansion coefficients of the core rod and the skin tube are quite different, and the matching between the two is poor, resulting in different shrinkage degrees of the core and skin glass during the cooling process after drawing; the core glass shrinks quickly, and the skin glass shrinks slowly, which causes stress concentration at the interface between the two, resulting in the problem of optical fiber breakage. Comparative Examples 1 to 5 have poor roundness of wire diameter after drawing. Observing the cross section of the single wire under a microscope, it can be seen that the core and skin are not tightly combined and there is a tiny gap. The reason may be that the softening temperature difference between the core and skin is too small, that is, the difference in the softening state of the core and skin glass is not significant, and the two are poorly matched, resulting in the two being unable to fuse with each other in the best state during drawing, resulting in poor roundness of wire diameter and core and skin separation, which reduces the structural strength and stability of the optical fiber inverter. Comparative Examples 7 to 8 leak light after being made into an optical fiber image transmission array. The reason may be that the softening temperature difference between the core and skin is too large, which makes the softening state of the core and skin glass significantly different during the drawing process, and the two are poorly matched; when the core glass has reached a good softening state for drawing, the skin glass has been over-softened, resulting in the two not being able to match well during flow and fusion, making the skin layer of the optical fiber thin during the drawing process, so that the transmitted light does not meet the total reflection condition due to the deformation of the core, resulting in optical fiber leakage.

[0099] The technical features in the claims and / or the specification of the present invention may be combined, and the combination is not limited to the combination obtained by reference in the claims. The technical solution obtained by combining the technical features in the claims and / or the specification is also within the protection scope of the present invention.

[0100] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A wide spectrum response radiation-resistant rod-tube assembly, comprising a core rod and a leather tube; the leather tube is sleeved on the outside of the core rod; characterized in that: The glass of the core rod has a spectral transmittance of ≥65% in the wavelength range of 330-2000nm when the thickness is 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a dose of 6.4kGy; the glass of the skin tube has a spectral transmittance of ≥75% in the wavelength range of 330-2000nm when the thickness is 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a dose of 6.4kGy; wherein the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the skin tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass is 10-25℃; the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃.

2. A method for preparing a wide spectrum response radiation-resistant rod-tube assembly, characterized in that: It includes the following steps: S21 raw materials are measured and mixed to obtain a core rod mixture and a leather tube mixture; S22: melting the core rod mixture and the skin tube mixture respectively, clarifying and stirring, discharging, casting and annealing to obtain a core rod or a skin tube; the glass of the core rod has a spectral transmittance of ≥65% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; the glass of the skin tube has a spectral transmittance of ≥75% in the wavelength range of 330-2000nm at a thickness of 100mm; the transmittance attenuation rate at 350nm is ≤3% after irradiation for 500h at a 6.4kGy irradiation dose; S23: The leather tube is placed on the outside of the core rod to obtain a rod-tube assembly; wherein the difference between the thermal expansion coefficient of the core rod glass and the thermal expansion coefficient of the leather tube glass is 1×10 -7 / ℃~10×10 -7 / ℃; the difference between the softening temperature of the core rod glass and the softening temperature of the skin tube glass is 10-25℃; the difference between the refractive index of the core rod glass and the refractive index of the skin tube glass is greater than 0.3; both the core rod glass and the skin tube glass remain chemically stable at 810℃.

3. The preparation method according to claim 2, characterized in that: In terms of mass percentage, the core rod mixture includes: 10-15% quartz sand, 20-30% boric acid, 19.5-30% lanthanum oxide, 1.1-10% zinc oxide, 1.1-10% niobium oxide, 10.1-20% barium carbonate, 0-3% hafnium oxide, 5.1-10% tantalum oxide, 1.1-7% yttrium oxide, 0-5% strontium carbonate, 0.5-7% aluminum oxide, 0-5% sodium carbonate, and 0.05-2% cerium oxide; the leather tube mixture includes: 60-75% quartz sand, 1.5-15% boric acid, 1-5% aluminum oxide, 1-10% sodium carbonate, 1-8% potassium hydrogen fluoride, and calcium fluoride. 1-8%, basic magnesium carbonate 0-5%, lithium carbonate 0-8%, zinc oxide 0-5%, cerium oxide 0-2%; in the core rod mixture and the tube mixture, the total content of impurities Fe, Cu and Mn is ≤3ppm; the total content of impurities Nd, Pr, U, Er, Eu, Tb, Dy is ≤2ppm; the instruments for preparing and melting the core rod mixture are all made of non-metallic alkali-resistant materials; the instruments for preparing and melting the tube mixture are all made of non-metallic materials; oxygen is introduced into the glass liquid during the melting, clarifying and stirring steps; the material of the melting furnace for melting and clarifying is refractory material, and its heavy metal content is ≤5ppm.

4. The preparation method according to claim 3, characterized in that: The container for melting the core rod mixture is a crucible made of magnesium oxide; the container for melting the leather tube mixture is a crucible made of quartz, and the surface of the crucible is provided with a silicon oxide coating.

5. The preparation method according to claim 3, characterized in that: The refractory material is a corrosion-resistant and high-temperature-resistant material, and its temperature resistance is ≥1700°C.

6. The preparation method according to claim 3, characterized in that: The melting furnace for melting the core rod mixture is dedicated to the preparation of the core rod glass; or the melting furnace for melting the skin tube mixture is dedicated to the preparation of the skin tube glass.

7. The preparation method according to claim 3, characterized in that: The mixed material is melted by adding the mixed material into the container in 3-5 times, each time at an interval of 0.5-2 hours.

8. The preparation method according to claim 3, characterized in that: The melting temperature of the core rod mixture is 1350-1400°C; the clarification and stirring temperature is 1460-1530°C, and the clarification and stirring time is 1-2h; the discharge temperature is 1300-1350°C; the annealing temperature is 550-600°C, and the annealing time is 2-4h; or, the melting temperature of the leather tube mixture is 1350-1400°C; the clarification and stirring temperature is 1460-1530°C, and the clarification and stirring time is 1-2h; the discharge temperature is 1300-1350°C; the annealing temperature is 550-600°C, and the annealing time is 2-4h.

9. The preparation method according to claim 3, characterized in that: When preparing the core rod, the flow rate of oxygen introduced into the glass liquid is 0.1-0.3 mol / L / min; or, when preparing the leather tube, the flow rate of oxygen introduced into the glass liquid is 0.04-0.18 mol / L / min.

10. Use of the wide spectral response radiation-resistant rod-tube assembly according to claim 1 in preparing a wide spectral response radiation-resistant optical fiber imaging array.

Citation Information

Patent Citations

  • Core-skin glass with good compatibility matching for optical fiber image transmission element and preparation method of core-skin glass

    CN115368011A

  • Hard fiber bundle blank plate and preparation method thereof

    CN116449487A

  • Ionization-irradiation-resistant light-induced thermal refractive glass, volume Bragg grating and preparation method of volume Bragg grating

    CN117776524A

  • Rare-earth doped phosphate-glass single-mode fiber lasers

    US20030152115A1

  • Glass substrate for display and display

    US20080206494A1